The Effect Of Educational Content On Surgical Readiness In Gen Z Patients Undergoing General Anesthesia At Yogyakarta City Hospital (HEALTH CARE: JURNAL KESEHATAN, 2026)
Background: Surgical readiness refers to patients’ physical and psychological preparedness for surgery and anesthesia. Preoperative education plays a crucial role in improving this readiness. For Generation Z, video-based educational media are considered more effective due to their digital preferences. Objective: To analyze the effect of educational content on surgical readiness among Gen Z patients undergoing general anesthesia at RSUD Kota Yogyakarta. Methods: This study employed a quasi-experimental design with a pretest-posttest control group approach. A total of 70 respondents were divided into experimental and control groups. Data were analyzed using the Wilcoxon signed-rank test and the Mann-Whitney test. Results: The experimental group demonstrated a significant improvement in surgical readiness from moderately ready to ready after the intervention (p